2017
DOI: 10.1007/s10103-017-2355-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser irradiation induces in vitro proliferation of stem cells from human exfoliated deciduous teeth

Abstract: The aim of this study was to evaluate the effect of low-level laser irradiation (LLLI) on the proliferation and viability of stem cells from human exfoliated deciduous teeth (SHED). Cells were irradiated or not (control) with an InGaAlP laser diode (660 nm, 30 mW, continuous action mode) using two different energy densities (0.5 J/cm-16 s; 1.0 J/cm-33 s). Irradiation was performed at 0 and 48 h, with the laser probe fixed at a distance of 0.5 cm from the cells. Cell proliferation was analyzed at 0, 24, 48, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…An up‐regulation of the Ki67 marker was observed following laser irradiation (56). Fernanda Ginani et al studied the effects of low‐power lasers on stem cells derived from human deciduous teeth and observed an increase in the expression of the Ki67 marker (57). However, our research shows that no studies have been performed on the effects of these two markers on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…An up‐regulation of the Ki67 marker was observed following laser irradiation (56). Fernanda Ginani et al studied the effects of low‐power lasers on stem cells derived from human deciduous teeth and observed an increase in the expression of the Ki67 marker (57). However, our research shows that no studies have been performed on the effects of these two markers on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that LLLT enhanced the viability and proliferation of ADSCs both in vitro and in vivo [5]. Other studies have reported positive effects of LLLT on stem cells [24,25].…”
Section: Discussionmentioning
confidence: 86%
“…MC3T3‐E1 preostoblastic cells (obtained from American Type Culture Collection [ATTC], USA) were cultured in an α‐MEM medium supplemented with 10% FBS and 1% antibiotic and antimycotic (100 IU/ml penicillin, 100 mg/ml streptomycin, and 0.25 μg/ml amphotericin B; all from Gibco, USA) and categorized into three groups: Group I (growth control)—cells cultured on a polystyrene plastic surface; Group II (PLA)—cells cultured on a PLA film and not submitted to laser irradiation; and Group III (PLA + Laser)—cells cultured on a PLA film and submitted to laser therapy. Cells in Group III were subjected to a single irradiation with an InGaAIP diode laser (Kondortech, Brazil) at 660 nm, 30‐mW power, 4.0 J/cm 2 energy density, using a 0.01‐cm 2 tip diameter, in continuous action mode, and plated in such a way that an empty well was present between seeded wells, in order to prevent unintentional light scattering between wells during laser application (Ginani, Soares, de Oliveira Rocha, de Souza, & Barboza, 2018). The irradiation probe was applied perpendicular to the plate at a 0.5‐cm distance from the cells and the PLA film.…”
Section: Methodsmentioning
confidence: 99%